Respuesta :
Answer:
[tex]y^{-9}\neq \dfrac{1}{y^{-9}}[/tex]
Step-by-step explanation:
Tyler simplified the expression: [tex]x^{-3}y^{-9}[/tex] as shown below:
[tex]x^{-3}y^{-9}=\dfrac{1}{x^3}X \dfrac{1}{y^{-9}}=\dfrac{1}{x^3y^{-9}}[/tex]
We notice that in Tyler's work:
[tex]y^{-9}= \dfrac{1}{y^{-9}}[/tex]
Whereas, the correct form would have been:
[tex]y^{-9}= \dfrac{1}{y^{9}}[/tex]
Making our solution:
[tex]x^{-3}y^{-9}=\dfrac{1}{x^3}X \dfrac{1}{y^{9}}=\dfrac{1}{x^3y^{9}}[/tex]
Answer:
Both powers should be in the denominator with positive exponents.